Differences, similarities and changes of national identity signs in print advertisements. The advertising discourse as a mirror of locality and vice-versa - Zantides, Evripides (My University, 2021)
The current paper aims to identify what kinds of nonverbal signs that conceptualise national identity are portrayed in print advertisements of the Republic of Cyprus since state independence from 1960 to 2010, as well as which ones are prevailing in an overall corpus of n=1860 advertisements. A methodological approach that utilizes quantitative content analysis and qualitative analysis, based on a semiotic interpretation of advertisements is implemented to withdraw results. While the findings of the study depict predominant cultural values and characteristics of the Cypriot national identity, a mapping of the nonverbal signs over time portrays which ones are affected or not, throughout the socio-political development of the island as a post-colonial, independent state. The paper shows that national credentials in print advertisements can, on the one hand, reflect values and characteristics of the people in a given culture, and on the other, portray differences, similarities and changes of locality in a reciprocal way over time.
Keywords: Advertisements; Cyprus; Qualitative analysis; Semiotic interpretation